Industrial training report: Soho Lekoi Restaurant And Cafe / Nur Addini Ahmad Jamil - Ahmad Jamil, Nur Addini (Universiti Teknologi MARA, Perlis, 2023)
Soho Lekoi is the second branch after the first successful branch Lekoi-Lekoi Restaurant & Cafe. It was founded on 9th January 2020 by Puan Camelia Ashikin with her husband at Bukit Chandan, Kuala Kangsar then relocated at Jalan Raja Idris, Kuala Kangsar during 16th January 2023. Soho Lekoi Restaurant & Cafe can be found near PPD Kuala Kangsar and Sekolah Kebangsaan Sultan Idris II. For a better address direction can be found in Google Maps or Waze. Meanwhile Lekoi-Lekoi is located near University Sultan Azlan Shah (USAS) and houses lot that make the shop always surrounded by different diverse customer backgrounds. Both of the restaurants are open from Monday to Saturday from 11am to 11pm. These restaurants currently have an average 3 up to 5 kitchen crew as well 4 to 6 service crew including the part timers. The founder of these restaurants sets a variety of menu covers from Asian fusion and western food. They also get onto specific international food preparation classes to make the menu more accurate to the original food taste, for example, nasi lamb xinjiang that originates from Xinjiang, China. There are a variety of food selections from Indonesia, China, India and Western. The signature menu at Soho Lekoi is their Nasi Lemak Pandan as it comes with variety type as the side dish such as telur mata, rendang kerang, rendang daging, crispy chicken chop, grill chicken chop, sambal grill sotong petai and many more. The signature menu at Lekoi-Lekoi is nasi ayam geprek where crispy fried chicken is eaten with the spicy Indonesian sambal alongside with crispy keropok and salad